2022
DOI: 10.36923/jicc.v22i4.95
|View full text |Cite
|
Sign up to set email alerts
|

An Intercultural Perspective on Subtitling Cultural Gaps for International Films: A Case of Fifteen Iranian Films

Abstract: Cultural products, particularly films, are considered tools for exporting and diffusing the culture of one society to another. Films selected for international festivals are a case in point. However, subtitling such films for an audience of other languages is a demanding task. This challenge may negatively impact the films' qualification, although they may technically and aesthetically be evaluated and ranked on top. The attraction of the films screened depends largely on how successfully certain features of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…On a practical level, this study highlights that training subtitlers can be effective in the production of optimal translations of cultural terms. As subtitles for films aim to globally disseminate cultural content, challenges related to culture and language could result in inadvertent loss or misinterpretation of the cultural essence of a film (Sanatifar & Ayob, 2022). Therefore, it is important to emphasize subtitling groups that possess intercultural competence to overcome language and cultural barriers, preventing loss or distortion of cultural content in films.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a practical level, this study highlights that training subtitlers can be effective in the production of optimal translations of cultural terms. As subtitles for films aim to globally disseminate cultural content, challenges related to culture and language could result in inadvertent loss or misinterpretation of the cultural essence of a film (Sanatifar & Ayob, 2022). Therefore, it is important to emphasize subtitling groups that possess intercultural competence to overcome language and cultural barriers, preventing loss or distortion of cultural content in films.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural references are specific words, phrases, or concepts that are associated with a particular culture or community. A relatively small number of scholars in translation studies, and even fewer in AVT, have proposed systematic definitions of CRs (Ranzato, 2015). However, Díaz-Cintas and Remael (2020) proposed that CRs are "items that are tied to a community's culture, history, or geography, and they can pose serious translation challenge " (p. 221).…”
Section: Cultural Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Azharbekova et al (2020) and Waters (2020) define cultural semantics as the meaning that a language has according to the culture of its speakers. Sanatifar, S. & Ayob (2022) also suggested that a language's lexicon reflects its cultural environment. In other words, cultural semantics translate the meaning of expressions so that the knowledge system is known and reflected in the mindset view of life and worldview of the cultural context in society (Dine, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of culture "originally referred to the humanist ideal of what was civilized in a developed society (e.g., music, art, food, and drink, dress, language, and so on)" [11]. Later it is described as how people live (e.g., rituals, traditions, etc.)…”
Section: When Culture and Language Are Treated As Separate Entitiesmentioning
confidence: 99%